Characterization of Shear Stress Mediated Platelet Dysfunction: Data from an Ex Vivo Model for Extracorporeal Circulation and a Prospective Clinical Study - Hidiatov, Oleg; Gaupp, Alisha; Marini, Irene; Pelzl, Lisann; Wagner, Miriam; Rigoni, Flavianna; Witzemann, Andreas; Häberle, Helene; Martus, Peter; Ngamsri, Kristian-Christos; Konrad, Franziska M.; Rosenberger, Peter; Straub, Andreas; Bakchoul, Tamam; Althaus, Karina (Thrombosis and Haemostasis, 2023)
Extracorporeal circulation (ECC) is frequently used in intensive care patients with impaired lung or cardiac function. Despite being a life-saving therapeutic option, ECC is associated with increased risk for both bleeding and thrombosis. The management of bleeding and thromboembolic events in ECC patients is still challenging partly due to the lack of information on the pathophysiological changes in hemostasis and platelet function during the procedure. Using a combination of an ex vivo model for shear stress and a sensitive and easy-to-use laboratory method, we analyzed platelet responsiveness during ECC. After shear stress simulation in an ex vivo closed-loop ECC model, we found a significantly decreased response of α-granules after activation with adenosine diphosphate and thrombin receptor activating peptide (TRAP-6) and CD63 expression after activation with TRAP-6. Mepacrine uptake was also significantly reduced in the ex vivo shear stress model.In the same line, platelets from patients under ECC with venovenous systems and venoarterial systems showed impaired CD62P degranulation after stimulation with ADP and TRAP-6 compared with healthy control on day 1, 6, and 10 after implantation of ECC. However, no correlation between platelet degranulation and the occurrence of bleeding or thromboembolic events was observed.The used whole blood flow cytometry with immediate fixation after drawing introduces a sensitive and easy-to-use method to determine platelet activation status and our data confirm that increased shear stress conditions under ECC can cause impaired degranulation of platelet.
Keywords: extracorporeal circulation; shear stress; chandler loop; α- and δ-granule; whole blood; platelet-rich plasma; extracorporeal membrane oxygenation